Meninjau persepsi pelajar kejururawatan ijazah tahun akhir dl Universiti Sains Malaysia terhadap pengajaran klinikal yang berkesan - Che Azunie, Che Abdullah (Universiti Sains Malaysia, 2008)
Clinical teaching is one of the most important parts in nursmg education. Unfortunately. there is still no convincing way to name which aspects is the most important in the contribution to the effectiveness of clinical teaching. So. the aim of this study is to survey students' perception on effective aspects of clinical teaching. This cross-sectional study involved 35 final year nursing students of University Science of Malaysia (USM). chose by purposeful sampling. Mean age of respondent is 22.5 which range from 22-23 years old. Questionnaire distributed was using 3 point Likert Scale to review students' perception on the topic. The result shows that the most important aspect is the characteristic of clinical instructor (2.67±0.34). follo\ved by clinical environment (2.65±0.23) and teaching strategy (2.24±0.31 ). For clinical instructor aspect. respondents feel that 'respect of students' right and dignity' is the most important criteria while in clinical environment aspect. 'support and guidance from the clinical staff' is considered as the most important one. The most important teaching strategy chose by the respondents is 'demonstration for the first time in clinical area'. In conclusion, facts on students' perception on the important aspects in clinical teaching should also be considered as one of enhancement material in nursing education in future for the sake of the effectiveness of clinical teaching and learning.